Wycena przedsiębiorstw metodą zdyskontowanych zysków netto - Zarzecki, Dariusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
If it can be assumed that relationship of net earnings (net income) to net cash flow is constant over time, then the formula to convert a discount rate applicable to net cash flow to a discount rate applicable to net income for use in the multiperiod discounted economic income model can be used. The formula is based on the critical assumptions stating that: 1) net income and net cash flow bear a constant relationship to each other over time, and 2) both grow at the same constant annually compounded rate in perpetuity. These critical assumptions for the conversion of a discount rate are rarely met in real world situations. Therefore, most authors recommend the use of net cash flow as the measure of economic income to use in the discounted economic income method. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 700-704